The Neighbors Respond : The Controversy over the Jedwabne Massacre in Poland - Michlic, Joanna B.; Polonsky, Antony (Book collections on Project MUSE., 2004)
Neighbors--Jan Gross's stunning account of the brutal mass murder of the Jews of Jedwabne by their Polish neighbors--was met with international critical acclaim and was a finalist for the National Book Award in the United States. It has also been, from the moment of its publication, the occasion of intense controversy and painful reckoning.